Directed sector and skill-specific technological change: The development of wages for the high and low skilled - Jürgen Antony (Universität Augsburg, Institut für Volkswirtschaftslehre, 2003)
This paper presents a dynamic two sector, two skill groups model of endogenous skill and sector specific technological change. The sectors refer to a high-tech” and a low-tech” sector of an economy. The direction of technological change is driven by market forces determined by the skill composition of the work force. It is shown that a change in this skill composition - a higher growth rate of the high skilled workforce in the high-tech” sector than in the low-tech” sector - leads to an increasing relative wage of the high skilled despite the fact that the aggregate supply of the high skilled might rise. This directed technological adjustment can easily overcome the usual substitution effect which would lead the relative wage to fall. The important result of the model is that the result does not depend on high values of the elasticity of substitution as necessary in other models of directed technological change, e.g. Acemoglu (1998, 2001). Further some of these models can be interpreted as special cases of the present model. Some open economy extensions show how effects of the mentioned change in the skill composition of the work force can spill over from one country to another if both countries engage in free trade and if the state of technology is determined globally.
urn:nbn:de:bvb:384-opus4-347309
Keywords: E25; J31; O31; F16; 330; wage inequality; directed technological change; endogenous growth; international trade